2008
DOI: 10.1177/0886260508314308
|View full text |Cite
|
Sign up to set email alerts
|

“The Red Zone”

Abstract: The "red zone" usually refers to the first few weeks of the first semester at college, when female students are believed to be at greatest risk for experiencing unwanted sex. We tested this notion using data from a survey study of 207 first-and second-year students (121 women, 84 men) at a small, liberal arts university. Results demonstrated only one significant elevation in incidence rates of first- and second-year women's unwanted sexual experiences (sexual touching, attempted and completed anal, oral, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
37
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 17 publications
11
37
2
Order By: Relevance
“…Incapacitation due to drugs or alcohol and use of force were the most common perpetrator tactics. The results are suggestive of a ‘red zone’ [2], whereby the occurrence of sexual victimization was higher among women who were recruited later in the academic year (winter semester) than earlier (fall semester). A comparison to the best U.S. studies conducted within the last 15 years confirm these findings [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incapacitation due to drugs or alcohol and use of force were the most common perpetrator tactics. The results are suggestive of a ‘red zone’ [2], whereby the occurrence of sexual victimization was higher among women who were recruited later in the academic year (winter semester) than earlier (fall semester). A comparison to the best U.S. studies conducted within the last 15 years confirm these findings [5].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the risk of sexual assault is particularly high for university women especially in the first year or two, which some authors have termed the ‘red zone’ [1,2]. In a representative sample of female students at Canadian universities, Dekeseredy and Kelly [3] found that more than one in four women have been sexually assaulted.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of hook up culture, Flack et al (2007) found that 23 % of women and 7 % of men reported one or more episodes of unwanted, possibly compliant sex since starting college. Moreover, Katz et al (2012) found that 16 % of women and 3 % of men reported complying with sex at least once within the first 2 months on campus; two-thirds of those who were compliant reported consenting to unwanted sex during a hook up.…”
Section: Introductionmentioning
confidence: 98%
“…While initially much of this received knowledge was based on anecdotes (e.g., see Ostrander & Schwartz, 1994), more recent empirical work supports the existence of a “red zone,” a time period of arguable length near the beginning of the student's time at college in which female students are at a heightened risk of sexual assault (Flack et al, 2008). While the literature on the red zone is still in its infancy, identifying the exact parameters of this time period and investigating the mechanisms underlying the temporal relationship are crucial for more effective institutional rape prevention efforts, allowing colleges to more effectively direct their rape prevention resources to contexts and student populations that are most at risk.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Some argue that the red zone covers the first year (Schwartz, 1997), and college materials on the red zone tend to emphasize this time period specifically (Flack et al, 2008). Empirically, Kimble, Neacsiu, Flack, and Horner (2008) use a sample of 50 first-year and 52 second-year students and find a significantly higher rate of victimization for first years, and Armstrong, Hamilton, and Sweeney (2006) use a qualitative approach to come to the same conclusion.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%